POTENSI HIDROKARBON FORMASI AIR BENAKAT, LAPANGAN ‘CA’, CEKUNGAN SUMATERA SELATAN - Prawoto, Adycipta Anis; Firmansyah, Yusi; -, Nurdrajat; Sunardi, Edy (Bulletin of Scientific Contribution, 2015)
Field ‘CA’ located in the South Sumatra Basin with an area of 6433 Km2. This study aimed to evaluate the hydrocarbon potential of Air Benakat Formation. Based on the results of the petrophysical analysis from well HA, BA, PA, RI and SE show the results are : Vsh cut off 0.34, Phie cut off 0.136 and SW cut off 0.59. Determination of reservoir netpay performed on HA well, that have thick of netpay 14.638 meters. The results of picking seismic horizon are time and depth structure maps of Air Benakat Formation and Gumai Formation. The map was made for determining lead in the research area. Calculation of estimated hydrocarbon reserves in the research area shows the value of OOIP is 345 MMBO.